Shifting driver of growth in Singapore : a VECM approach - Ang, Joshua Wei Zhang (2019)
In this report, we analysed the internal and external engine of growth in both short run and long run of Singapore using the Vector Error Correction Model (VECM). We derived significant statistical results indicating that Gross Fixed Capital Formation (GFCF), manufacturing output (MFU), Foreign Direct Investment in manufacturing (FDIMFU) and major trading partner’s GDP (TPART) have long run association with Singapore’s GDP. Based on the short run VECM results, we find that GFCF, manufacturing output and trading partner’s GDP are good predictors to Singapore’s GDP. We run Wald test and found out that Singapore’s GDP has causality with manufacturing output and trading partner’s GDP. This represent the internal and external engine respectively. From the short run coefficients, we can tell that manufacturing (internal engine) affect Singapore’s GDP twice as much as trading partner (external engine). Through impulse response analysis, we found that all variables have positive and permanent impacts on GDP. On a shorter horizon, GFCF appears to decay fast and sharp after 2 periods. On a longer horizon, manufacturing and FDI in manufacturing appears to generate multiplied effects on GDP through positive spill over effects into the economy. Our results are being supported through the variance decomposition technique that shows that in the short run, shocks to GDP were mainly accounted by external driver but in the long run, manufacturing and FDI in manufacturing accounts for the majority in variation to the shocks.